2019
DOI: 10.1093/hmg/ddz265
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contribution to the cognitive alterations in SCA1: evidence from mouse models

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a fatal neurodegenerative disease caused by abnormal expansion of glutamine (Q) encoding CAG repeats in the gene Ataxin-1 (ATXN1). Although motor and balance deficits are the core symptoms of SCA1, cognitive decline is also commonly observed in patients. While mutant ATXN1 is expressed throughout the brain, pathological findings reveal severe atrophy of cerebellar cortex in SCA1 patients. The cerebellum has recently been implicated in diverse cognitive functions, yet to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 95 publications
3
20
0
Order By: Relevance
“…Mice can solve Barnes maze using spatial and non-spatial search strategies, or by randomly exploring the maze using no strategy at all ( Supplementary Figure 12 ). We have previously shown that Atxn1 154 Q/ 2 Q mice preferentially use random and serial strategies instead of spatial strategies to find the escape hole implicating deficits in developing higher level cognitive strategies [11]. Using BUNS, we found that BDNF significantly improved strategy development in Atxn1 154Q /2Q mice (from 6.25% use of spatial search strategies including direct, corrected, long corrected and focused search in aCSF to 18% in BDNF treated mice, Figure 6E ).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Mice can solve Barnes maze using spatial and non-spatial search strategies, or by randomly exploring the maze using no strategy at all ( Supplementary Figure 12 ). We have previously shown that Atxn1 154 Q/ 2 Q mice preferentially use random and serial strategies instead of spatial strategies to find the escape hole implicating deficits in developing higher level cognitive strategies [11]. Using BUNS, we found that BDNF significantly improved strategy development in Atxn1 154Q /2Q mice (from 6.25% use of spatial search strategies including direct, corrected, long corrected and focused search in aCSF to 18% in BDNF treated mice, Figure 6E ).…”
Section: Resultsmentioning
confidence: 73%
“…A number of studies demonstrate that mild cognitive deficits, including visuospatial and memory dysfunctions are present in some patients with SCA1 [47][14][48][49][50][51][52]. Previous studies described impaired performance of Atxn1 154 Q/ 2 Q mice in cognitive tests including Morris Water Maze, Barnes maze, and contextual fear conditioning at 7-12 weeks of age [10][11]. Neuronal dysfunction and neuronal loss in the hippocampus were described at 24 weeks [10][12] and hippocampal neurogenesis was reduced at 12 weeks in Atxn1 154 Q/ 2 Q mice [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PolyQ expansion in ATXN1 leads to both gain and loss of ATXN1 function 44,45 . Gain-of-function is the predominant molecular mechanism of motor deficits in SCA1, as supported by the lack of a strong motor phenotype in Atxn1 null mice 25,27 , while lossof-function may contribute to cognitive deficits 17,27 . We therefore wanted to determine whether loss of ataxin-1 alters mood in Atxn1 −/− mice.…”
Section: Resultsmentioning
confidence: 97%
“…Mouse models of SCA1 have been essential in implicating cerebellar pathology and gain-of-function mechanisms in ataxia and cognitive deficits 17,[25][26][27] . For instance, motor deficits in the transgenic SCA1 mouse line ATXN1 [82Q], which overexpress mutant ATXN1[82Q] protein selectively in cerebellar Purkinje cells, provided support for the predominant role of cerebellar dysfunction in ataxia 28 .…”
mentioning
confidence: 99%